EFISIENSI SKALA USAHATANI PERKEBUNAN KELAPA SAWIT DAN DISTRIBUSI PENDAPATAN PETANI DI PROPINSI KALIMANTAN TIMUR - Daroni Daroni; Sri Widodo; Dwidjono Hadi Darwanto; Sofyan P Warsito (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2004)
The objective of this research is to study the farmscale efficiency of oil palm smallholders. In this context it will also be studied the change in shifting cultivation activity and distribution of oil palm farmer income.The research was done in East Kalimantan with samples of 350 farmers by